Electric Field Manipulation of Magnetization Rotation and Tunneling Magnetoresistance of Magnetic Tunnel Junctions at Room Temperature - Li, Peisen; Chen, Aitian; Li, Dalai; Zhao, Yonggang; Zhang, Sen; Yang, Lifeng; Liu, Yan; Zhu, Meihong; Zhang, Huiyun; Han, Xiufeng (Advanced materials (Weinheim), 2014)
Electric‐field‐controlled tunneling magnetoresistance (TMR) of magnetic tunnel junctions is considered as the milestone of ultralow power spintronic devices. Here, reversible, continuous magnetization rotation and manipulation is reported for TMR at room temperature in CoFeB/AlOx/CoFeB/piezoelectric structure by electric fields without the assistance of a magnetic field through strain‐mediated interaction. These results provide a new way of exploring electric‐field‐controlled spintronics.